Features of the microbiota of the urogenital tract of women with pathological conditions - Bezkrovna, Y. M.; Golodok, L. P.; Vinnikov, A. I. (Regulatory Mechanisms in Biosystems, 2017)
Nonspecific infection of the female reproductive system continues to occupy the first place among pathologies of the reproductive tract of the female. These diseases affect the organs and tissues related to the reproductive system. Using the method of polymerase chain reaction in real time, we investigated characteristics of the normal and conditionally pathogenic aerobic / facultative anaerobic, anaerobic biota in the urethra, cervical canal and vagina of women aged 16 to 58 years, studies were carried out on the basis of the Center of Laboratory Diagnostics, LLC "MEDLAYF". For all women up to the age of 40, biota is mainly represented by lactobacilli (Lactobacillus spp.), and in pathological complications of the urogenital tract of women the microbial composition of the biocoenosis is characterized by a decrease in the number of lactobacilli and their replacement by pathogenic anaerobic microorganisms. In disorders of the microflora of the urogenital tract we also detected the human papillomavirus of both high and low carcinogenic risk and Ureoplasma (urealiticum + parvum), Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma hominis and yeast of the genus Candida spp. The most frequently distributed of the most common causative agents of pathological conditions of the reproductive system of women is the human papillomavirus of high carcinogenic risk, Ureoplasma (urealiticum + parvum) and Candida spp. This is due to anatomical and physiological characteristics of the genital organs, hormonal and immune system.